2019
DOI: 10.1039/c8cp06198j
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced changes in atomistic mechanisms for the Cl + CH3I SN2 reaction with increasing collision energy

Abstract: A sudden change from indirect to direct mechanism for Cl− + CH3I at Erel of 0.27–0.28 eV in a relatively small collision energy range of 0.15–0.40 eV is revealed and many indirect mechanisms are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…QCEIMS combines quantum chemical methods and statistical mechanics concepts 29,42 . This use of molecular dynamics to model mass spectrometry is relatively new and was pioneered by the late Bill Hase 31,42–45 . The International Journal of Mass Spectrometry recently dedicated a memorial issue to his contributions for the mass spectrometry field 46 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QCEIMS combines quantum chemical methods and statistical mechanics concepts 29,42 . This use of molecular dynamics to model mass spectrometry is relatively new and was pioneered by the late Bill Hase 31,42–45 . The International Journal of Mass Spectrometry recently dedicated a memorial issue to his contributions for the mass spectrometry field 46 …”
Section: Methodsmentioning
confidence: 99%
“…29,42 This use of molecular dynamics to model mass spectrometry is relatively new and was pioneered by the late Bill Hase. 31,[42][43][44][45] The International Journal of Mass Spectrometry recently dedicated a memorial issue to his contributions for the mass spectrometry field. 46 T A B L E 1 Novichok family nerve agents added to the CWC 6…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the QCEIMS program extended to determine CID spectra was renamed as QCxMS [37][38][39]. Although MD methods to simulate CID experiments have been proposed before [33,[40][41][42][43], now explicit collisions between ions and collision gas could be included in a friendly and accurate software specifically designed to determine CID mass spectra from MD simulations [37].…”
Section: Introductionmentioning
confidence: 99%
“…10 Backward scattered events are characteristic of the direct rebound mechanism known for S N 2. [11][12][13][14] However, Wester et al 9 reported that less than half of the reactive collisions follow the direct rebound mechanism and the forward scattered ions exhibit a narrow range of product angle for CN À + CH 3 CH 2 I reaction at E coll = 1.9 eV by using crossed beam velocity map imaging. Thus, the competitive results of E2 and S N 2 reactions are still indistinct.…”
Section: Introductionmentioning
confidence: 99%